Islamic Estate Planning in the industrial revolution era 4.0: Issues and challenges. / Muhamad Muizz Abdullah ... [et al.] - Abdullah, Muhamad Muizz; M. Fariddudin, Siti Noor Farahin; Nor Muhamad, Nasrul Hisyam; Awang, Abdul Bari (Universiti Teknologi MARA, 2021)
The development of the Industrial Revolution 4.0 has contributed to creating various technologies for economic progress. This includes the field of Islamic estate planning, such as will and trust. However, the technology developed to meet the Muslim community's property planning needs is still in its infancy until now. Therefore, the purpose of this study is to investigate the issues and challenges faced by trust institutions in Malaysia in facing Islamic estate planning in the Industrial Revolution 4.0 era and its effect on Muslim community. This study uses a content analysis approach by reviewing and analyzing previous Islamic estate planning studies. To achieve the goals of the study, this study refers to the classical and secondary sources in the field of expert. Furthermore, five official websites from 5 trust institutions; Amanah Raya Berhad (ARB), as-Salihin Trustee Berhad, Wasiyyah Shoppe Berhad, MyAngkasa Berhad and the Islamic Religious Council (Selangor) (MAIN) were analyzed to obtain information on the current will and trust practice. Several representatives of officials from each selected institution were interviewed to obtain more accurate information. The study found that the implementation of Islamic estate planning through digital technology in line with the era of Industrial Revolution 4.0 is still in the early stage, starting only from 2018. This is because its manual implementation through human resources is still required while manual trust documentation is still maintained. Therefore, it is hoped that the trust institutions may provide new mechanisms and fresher innovations in encouraging the community to implement will and trust in line with Industrial Revolution 4.0